Respuesta :

We must transform triangle ABC.

In part (a) the transformation that we must apply is:

[tex](x,y)\rightarrow(x-4,y+1)[/tex]

Now we take the three points A, B and C and we apply the transformation to them. The resulting points will be the vertices of triangle T. Then we get:

[tex]\begin{gathered} A=(2,3)\rightarrow(2-4,3+1)=(-2,4) \\ B=(4,2)\rightarrow(4-4,2+1)=(0,3) \\ C=(3,5)\rightarrow(3-4,5+1)=(-1,6) \end{gathered}[/tex]

Then triangle T and the answer to part a is:

In part b we must use this transformation:

[tex](x,y)\rightarrow(-x,y)[/tex]

We apply this transformation to A, B and C:

[tex]\begin{gathered} A=(2,3)\rightarrow(-2,3) \\ B=(4,2)\rightarrow(-4,2) \\ C=(3,5)\rightarrow(-3,5) \end{gathered}[/tex]

Then triangle R and answer to part b is:

Ver imagen TiaraS721596
Ver imagen TiaraS721596